Immune Cell Infiltration in Feline Meningioma. Issue 2 (February 2017) - McBride, R.; Sloma, E.A.; Erb, H.N.; Miller, A.D.
Summary: Meningioma is the most common primary brain tumour in the cat. Although most of these tumours are considered to be benign based on histological characteristics, little is known regarding microenvironmental changes associated with the tumour. The characterization of the immune-cell infiltrate in human and canine meningiomas has been described; however, there are no data regarding the cat equivalent. Seventeen formalin-fixed, paraffin wax-embedded samples of feline meningioma were evaluated by light microscopy and immunohistochemistry (IHC) for expression of CD3, Pax5, Iba-1, HLA-DR, MAC387, CD163 and Ki67. Variable immune cell infiltrates were seen in every case. All tumours had moderate numbers of infiltrating CD3 + T lymphocytes. Seven of 17 tumours (41%) had infiltrating PAX5 + B lymphocytes that were often dispersed randomly throughout the neoplasm. Macrophage infiltration was abundant in all tumours with widespread immunoreactivity for Iba-1 and HLA-DR. Most tumours (15/17; 88%) had infiltration by MAC387 + macrophages; however, the number of infiltrating cells per ×400 field varied widely (from 0 to 57). Thirteen of 17 tumours (76%) had infiltration by CD163 + macrophages; however (similar to the MAC387 IHC), several tumours had numerous infiltrating cells. There was a potential weak negative rank correlation between the counts of CD3 and Ki67 + cells (rSp  = −0.57; P  = 0.018); however, no other rank correlations could be established between types of infiltrating immune cells (all other P  ≥0.10). This study establishes evidence for a robust population of immune cells in feline meningioma and indicates that further study is needed to better understand the role of these cells with respect to tumour progression and post-surgical outcome.